A Review on Multiple Single Hop Clustering Based Data Transmission in Wireless Sensor Network (International Journal of Engineering and Computer Science, 2014)
The most important objectives of wireless sensor network are to enhance or to increase the lifetime of the sensor network and also to use the energy of the network effectively. Many traditional approaches had been proposed in wireless sensor network (WSN) to achieve these objectives. But, they are not so eﬃcient and reliable in terms of utilization of energy on the network nodes. However, nodes in network are typically considered to be homogeneous in nature since the researches in the field of wsn have been evolved but in real world, homogeneous sensor networks hardly been considered for research. Thus, we require a clustering technique which will work in heterogeneous environment which are more closely relates with real life environment. In this paper, there isreview of energy protocolswhich are used in wsn and also defined the keyfactors required for efficient data transmissioon or communication. Along with it this paper also include the improvement proposal in sensor network in energy conservation. This will consume less energy in long distance communication than previous single hop protocols which also help in lifetime enhancement.